EFEKTIVITAS GAYA KEPEMIMPINAN TRANSFORMASIONAL DI PT. SEBASTIAN CITRA INDONESIA - Risa Lailatul Maqviroh; Dewi Lestariningsih; Tasya Nabila Al Zahra Putri; Sa’diyah Qurrotul A’yuni; Anang Sugeng Cahyono (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The purpose of this study is to analyze and discuss the effectiveness of transformational leadership at PT Sebastian Citra Indonesia. A company engaged in retail food and beverage which is one of the frozen dough producers supplied to outlets with the Roti'O brand. Transformational leadership has been recognized as an effective approach in creating positive change within organizations. The research method used is a qualitative approach by conducting in-depth interviews with employees. The collected data was analyzed using descriptive analysis and interpretive approaches to identify emerging patterns and themes related to transformational leadership. The results showed that transformational leadership indicators (Intellectual Stimulation and Individual consideration) have been effectively applied. Leaders in this company have conveyed a vision and mission to their employees, a deep understanding of individual needs, and the ability to create a collaborative and innovative work climate. But in the ideal influence and work motivation has not been applied to the maximum